(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the verbal and nonverbal expressions of affirmation and negation in two distinct linguistic and cultural contexts: Uzbek and English. Through a comparative lens, the study highlights both the similarities and cultural nuances that shape how speakers of each language express agreement and disagreement, acceptance and rejection. The discussion draws upon examples from daily interactions, linguistic structures, and cultural practices.